Social Impact in Social Entrepreneurship : Conceptualization, Manifestation, and Measurement - Polychronopoulos, Georgios; Lukeš, Martin, 1976-; Dvouletý, Ondřej; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This doctoral dissertation comprises a set of three interrelated scientific articles that collectively advance theoretical understanding of social impact within the context of social entrepreneurship. The first article, a systematic integrative review, clarifies the concept of social impact, delineating its theoretical underpinnings and proposing a theoretical framework towards a programmatic theory of social impact. The second article, a comparative qualitative study, develops an outcome-based typology of social enterprises, highlighting the varied ways in which these ventures create social impact. The third article, a quantitative study, empirically examines the drivers of social impact measurement practices in nascent social enterprises, illuminating imprinted organizational characteristics that influence the adoption of these practices.
Vedoucí práce: Martin Lukeš
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management and managerial economics [obor disert. práce]; disertace; dissertations